(untitled) (Research, Society and Development, 2020)
The incidence and prevalence of the treatment of acute or even chronic wounds shows that the psychological, social and economic impact of the chronicity of injuries, especially infected ulcers, represents the second cause of absence from work, indicating the need to develop more advanced technologies. simple and lower cost materials used as effective dressing bases to make them accessible to a greater number of people, as one of the challenges for the public manager is the high operational cost, since most of the components used in wound coverings it is imported and with technology patented by multinational companies. In this sense, the present work aimed to reduce costs in the preparation techniques and asepsis of bullfrog skin (Lithobates catesbeianus) to enable its use as biomaterial in a dressing bed due to the presence of peptides with antibiotic action. The method of processing, decontamination and sterilizing the skin of the bullfrog was carried out by autoclaving. The results of the microbiological analyzes on the pulverized and autoclaved bullfrog skin allowed us to verify that this type of material sterilization was satisfactory, not registering the presence of microbial agents that would prevent its use as a dressing bed.